IMPLEMENTASI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA PADA PEMILIHAN KUWU DI KABUPATEN INDRAMAYU TAHUN 2021 - Rasji Rasji; Gunardi Gunardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Indonesia has the lowest government in rural areas which is called village administration. In Indramayu Regency, the village administration is led by a Kuwu. Kuwu is elected by the villagers through the kuwu election mechanism. The election of village heads has been regulated in Law Number 6 of 2014 concerning Villages. In 2021 the Indramayu Regency Government will hold Kuwu elections for 171 villages. The election for kuwu in Indramayu Regency must refer to Law Number 6 of 2014 but its implementation is faced with the conditions of the Covid-19 pandemic. How is the implementation of Law Number 6 of 2014 concerning Villages in the Kuwu election in Indramayu Regency? This is the problem that is discussed and used in this article. The aim is to find out the implementation of Law Number 6 of 2014 concerning Villages in the Kuwu election in Indramayu Regency during the Covid-19 pandemic. These problems have been researched using empirical legal research methods through observations and interviews. The results showed that the Indramayu Regency government modified the implementation of Law Number 6 of 2014 concerning Villages in the Kuwu election in Indramayu Regency according to the Covid-19 pandemic conditions. The results of this study contribute to the development of village government laws and research programs organized by Tarumanagara University